Penghukuman dan Inklusi dalam Markus 11:15–19: Pembacaan Naratif atas Interkalasi Pohon Ara dan Penyucian Bait Allah - Henky Purwanto; Lukas Widiyanto (Sekolah Tinggi Teologi Kalvary - Maluku Utara, 2026)
Understanding the theological message of the Bible requires careful attention to narrative context and to the distinctive character of each Gospel. In the account of the cleansing of the Temple, common interpretations often emphasize the holiness of God’s house or the replacement of the Temple cult with Jesus himself as the new center of worship. While such readings are not entirely incorrect, they do not sufficiently take into account the distinctive narrative strategy of the Gospel of Mark. This article seeks to examine the theological meaning of the cleansing of the Temple in Mark 11:15–19 by reading it in structural and narrative connection with the cursing of the fig tree. Employing narrative analysis through the technique of intercalation (sandwich), this study argues that Mark is not primarily concerned with issues of worship alone, but deliberately frames the Temple incident as a symbolic act of judgment against the unfruitfulness of Israel. Moreover, this narrative structure also introduces an inclusive dimension, in which the critique of the Temple is closely related to Mark’s vision of an open space of worship for the nations. These findings demonstrate that the cleansing of the Temple in Mark functions as a declaration of theological judgment as well as a redefinition of the people of God, offering an important contribution to narrative readings of the Gospel of Mark and to contemporary ethical–theological reflection. Abstrak Memahami pesan teologis dalam Alkitab menuntut pembacaan yang cermat terhadap konteks naratif dan kekhasan masing-masing Injil. Dalam kisah penyucian Bait Allah, penafsiran yang umum sering kali menekankan tema kekudusan rumah Allah atau penggantian kultus Bait Allah dengan pribadi Yesus sebagai pusat penyembahan yang baru. Meskipun tidak sepenuhnya keliru, pendekatan tersebut belum secara memadai memperhatikan strategi naratif khas Injil Markus. Tulisan ini bertujuan menelaah makna teologis kisah penyucian Bait Allah dalam Markus 11:15–19 dengan menghubungkannya secara struktural dan naratif dengan peristiwa pengutukan pohon ara. Dengan menggunakan pendekatan analisis naratif melalui teknik intercalation (sandwich), studi ini menunjukkan bahwa Markus tidak semata-mata menyoroti isu penyembahan, melainkan secara sengaja membingkai peristiwa tersebut sebagai tindakan simbolik penghukuman terhadap ketidakberbuahan Israel. Lebih jauh, struktur naratif ini juga membuka dimensi inklusif, di mana kritik terhadap Bait Allah berkaitan dengan visi Markus mengenai keterbukaan ruang ibadah bagi bangsa-bangsa lain. Temuan ini menegaskan bahwa penyucian Bait Allah dalam Injil Markus berfungsi sebagai deklarasi penghakiman teologis sekaligus redefinisi umat Allah, yang memberi kontribusi penting bagi pembacaan naratif Injil Markus dan refleksi etis-teologis pembaca masa kini.